Antagonistic bacteria with potential for biocontrol on Rhizopus stolonifer obtained from blackberry fruits. (28th January 2014) - F. Chávez-Díaz, Ismael; Angoa-Pérez, Valentina; López-Díaz, Sigifredo; G. Velázquez-del Valle, Miguel; N. Hernández-Lauzardo, Ana
<x content-type="archive" xml:space="preserve">Abstract</x> Introduction. México is one of the most important producers and exporters of blackberries in the world. During postharvest handling, blackberry fruits are exposed to the attack of phytopathogenic fungi. Materials and methods. To obtain Rhizopus stolonifer isolates, samples of leaves and rhizospheric soils were placed on Petri plates containing Potato Dextrose Agar (PDA). In addition, fruits were also placed in humidity chambers at 25 °C. To describe the infection process on blackberry fruits by Rhizopus stolonifer, samples were taken at different intervals for a period of 72 h. All fungal isolates obtained were maintained on PDA. The bacterial colonies were isolated and purified by streaking on PDA. The antagonistic activity of the bacteria was assessed against R. stolonifer by dual culture technique on PDA. To detect the production of siderophores, the chrome azurol S assay was carried out. Results. The infection process of R. stolonifer on blackberry fruits was described for the first time in this work. Eighty-six bacterial isolates from different parts of the plant and rhizospheric soil were obtained. Bacterial isolates with antagonistic activity were identified and the production of siderophores was measured. Four isolates showed antagonistic activity against R. stolonifer. Bacillus subtilis obtained from soil was the most effective isolate. Conclusion. In this study we isolated and identified antagonistic bacteria with potential for biocontrol on Rhizopus stolonifer obtained from blackberry fruits. To our knowledge this is the first report regarding this topic.